Media Capital : Architecture and Communications in New York City - Wallace, Aurora (Book collections on Project MUSE., 2012)
With a unique focus on corporate headquarters as embodiments of the values of the press and as signposts for understanding media culture, this book demonstrates the mutually supporting relationship between the media and urban space.